Forrageamento em espécies de aranhas cleptoparasitas e araneofágicas invasoras de teias de Manogea porracea (Araneae: Araneidae) - Meira, Felipe André (2018)
Many spider species build webs and remain resting on this structure to capture prey. In addition, the transmission of vibrational stimuli on webs is involved with the identification of sexual partners and the silk may act like a physical barrier that minimizes predation risk. Nevertheless, the web can be used by intruder, kleptoparasite spiders, and may allow access to araneophagic predators. In this study we observed an araneophagic species, Gelanor zonatus, and two species usually considered as kleptoparasites, Faiditus caudatus and Argyrodes elevatus, invading webs of Manogea porracea. We tested hypotheses on trophic position of intruders and their nutritional preferences. We also evaluated factors that influence their occurrence on host webs and the biomass acquired by the araneophagic predator after the consumption of different prey items. We conducted tests with nitrogen and carbon stable isotopes, field observations and laboratory experiments. Gelanor zonatus shows higher values of nitrogen isotopes when compared with other species found in the same area. It can, consequently, be considered as a secondary carnivore predator. This species shows diet selectivity based on their prey nutricional content. Furthermore we observed that the increase in predator body mass, when it consumes different prey items, varies not only with the prey mass, but also with prey species. Kleptoparasites show nitrogen isotopes values similar to Gelanor zonatus and higher than host spider species. The presence of males, females or both and the egg sacs on M. porracea webs did not explain the kleptoparasite occurrence. Finally, A. elevatus exhibit preference for prey consumption instead of eggsacs on the invaded webs.